The behavior of enclosed-type connection of drill pipes during percussive drilling; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Shadrina A. V. Anastasiya Viktorovna (Latest Technology of Oil and Gas Driling, 2015)
Title screen